Desain, Implementasi Dan Evaluasi Sistem Informasi Penggajian Di Universitas Berbasis Web - Villy Satria Praditha; Ario Harry Prayogo; Anranur Uwaisy Marchiningrum; Feddy Dea Reskyadita; Nurjayanti Nurjayanti; Utami Kusuma Dewi; Ryan Lingga Wicaksono (Jurnal Informasi, Sains dan Teknologi, 2024)
The university's payroll process includes information about various employees, including lecturers and administrative employees with varying details such as personal data, position and salary information. This research is focused on rebuilding the payroll application due to several shortcomings or challenges associated with the existing application. This research presents a detailed investigation into the design, implementation, and evaluation of a payroll application tailored for the university environment. This research covers main aspects such as use case analysis, relational database schema, application display and testing. Use case analysis begins with identifying and understanding the various scenarios and requirements specific to a university payroll system. Through thorough exploration of user roles, system functionality. Relational database schemas are designed to efficiently store and manage complex payroll data, ensuring accurate and efficient processing. Compatibility testing plays an important role in ensuring the integration of payroll applications with existing systems. This research performs black-box testing to test application functionality and application compatibility testing with various hardware configurations, operating systems, and web browsers to ensure optimal performance and accessibility. The results of this research contribute to the advancement of payroll management and provide guidance for the development of deep payroll applications in universities.